2022-RA-1074-ESGO AGO-OVAR 2.29 (ENGOT-ov34): atezolizumab in combination with bevacizumab and chemotherapy vs bevacizumab and chemotherapy in recurrent ovarian cancer. (20th October 2022) - Harter, Philipp; Marmé, Frederik; Pietzner, Klaus; Reuss, Alexander; Ray-Coquard, Isabelle; Redondo, Andrés; Oaknin, Ana; Jonuskiene, Goda; Lindemann, Kristina; Kurzeder, Christian; Huober, Jens; van Nieuwenhuysen, Els; et al.
Abstract : Introduction/Background: Paclitaxel or pegylated liposomal doxorubicin (PLD) in combination with bevacizumab constitutes a standard treatment option in patients with relapsed ovarian cancer (ROC) who are not considered candidate for platinum, but responses are short-lived. Immune-checkpoint inhibitors like atezolizumab as single agents have limited activity in ovarian cancer. There is a biologic rationale to combine checkpoint inhibitors with chemotherapy and bevacizumab, however, the role of such combination for the management of ovarian cancer is so far undefined. Because of the intimate relationship between angiogenesis and immunosuppression, it is expected that inhibition of both pathways could lead to synergism and more durable clinical benefit. The addition of a chemotherapeutic agent is expected to lead to the release of tumor antigens and enhance the efficacy of immunotherapy. Therefore, we aim to test the efficacy of atezolizumab in combination with non-platinum-based chemotherapy and bevacizumab vs the combination of a non-platinum-based chemotherapy and bevacizumab alone. Methodology: AGO-OVAR 2.29 is a randomized (1:1), double-blinded, phase III trial evaluating the efficacy and safety of atezolizumab plus bevacizumab and chemotherapy (weekly paclitaxel or PLD) compared with placebo, bevacizumab and chemotherapy in patients with recurrent ovarian, fallopian tube, or primary peritoneal cancer with 1st or 2nd relapse within 6 months after completing platinum-based chemotherapy or 3rd relapse. Patients are treated until progression or unacceptable toxicity. A de novo tumor biopsy to determine the PD-L1 expression status prior to randomization for stratification is mandatory. Co-primary endpoints are overall survival and progression-free-survival. Target recruitment is 550 patients. Safety interim analyses were performed after inclusion of 24, 60 and 120 patients who had completed at least one cycle. Results: Screening was stopped on 23-May-2022. As of 30-May-2022, 554 patients have been randomized. Conclusion: This concept might open the possibility to investigate the synergetic effect of immune-checkpoint and angiogenesis inhibitors in ROC.